Therapeutic significance of aestheticisation of affect in the sychosomatics of personality development - Robert Dobrowolski; Katarzyna Salamon-Krakowska (Physiotherapy Quarterly, 2018)
Both in the physiotherapeutic practice and artistic activity-based therapy, apart from purely somatic disorders, we often encounter the impairment of mentalizing abilities. Patients cannot express their sensations, feelings, or affects. As evidenced by the psychoanalytical theory developed on the basis of a substantial clinical material, this can lead to psychosomatic disorders. Their treatment, involving activities and methods that help reinforce the patient’s ability to aesthetically experience their own psychophysicality as a harmoniously connected unity, turns out to be extremely useful. It is thanks to art and aesthetic experiences that we gain access to these aspects of our psychophysical condition, which are unaccounted by abstract analysis. Our aesthetic experience reveals mainly the unconscious and affective components of our life attitude. Moreover, these kinds of experiences allow us not only to recognize our psychosomatic conditions as well as problems that we experience, but also to effectively and somaesthetically work with them. The art-based therapy and artistic activities allow the harmonizing experience of unity of the emotional and physical with the intellectual and symbolic, and thus open up the opportunity to regain a deep sense of meaningfulness.